Biomarkers of oxidative-stress and inflammation in exhaled breath condensate from hospital cleaners. (17th February 2016) - Casimirri, Enrico; Stendardo, Mariarita; Bonci, Melissa; Andreoli, Roberta; Bottazzi, Barbara; Leone, Roberto; Schito, Michela; Vaccari, Alice; Papi, Alberto; Contoli, Marco; Corradi, Massimo; Boschetto, Piera
Abstract: Objective : We studied the impact of chlorinated agents exposure on exhaled breath condensate (EBC) biomarkers in cleaners. Methods : Malondialdehyde (MDA), 4-hydroxynonenal (4-HNE), nitrites ( ), nitrates ( ), pH, hydrogen peroxide (H2 O2 ) and ammonium ( ) were tested in EBC of 40 cleaners and 40 non-exposed controls. Pentraxin-3 (PTX3) and soluble type II receptor of IL-1 (sIL-1RII) were analyzed also in plasma. Results : Levels of MDA-EBC, 4-HNE-EBC and -EBC were higher, while pH-EBC values were lower, in cleaners. MDA-EBC was associated with 4-HNE-EBC, -EBC and pH. 4-HNE-EBC correlated with PTX3. Conclusion : Professional exposure to chlorinated agents increases EBC biomarkers of oxidative stress and inflammation.